A state of inequality: confronting elite capture in post-conflict Guatemala - Stine, Kelsi R. (Tufts Archival Research Center, 2005)
Submitted in partial fulfillment of the degree of Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: State capture is a type of corruption that deserves more attention in the international policy sphere. This thesis analyzes how Guatemala's oligarchy captures public decision making processes in order to shed light on how the international community can more proactively address state capture. It first provides a contextual overview of corruption and state capture, arguing that corruption is an inherently political and highly contextual concept. Guatemala is used as the primary focus of analysis because its history of Spanish colonialism, marginalization of indigenous communities, repressive military governance, and economic monopolization has created an environment of extreme state capture. The main case study illuminates how Guatemala's oligarchy succeeded in keeping land reform out of the 1996 peace process as an example of how other state processes in the post-conflict period are similarly captured. Ultimately, efforts to address state capture have to be political in order to work; the current system of providing international technical assistance is ineffective. However, political solutions to state capture remain generally untested, and require accurate state capture diagnosis, further research, and gradual implementation.